하번초형 혼파조합간의 건물수량, 사료가치 및 식생비율 비교연구 - 이중해; 이인덕; 이형석; Lee, Joong-Hae; Lee, In-Duk; Lee, Hyung-Suk (Journal of animal science and technology, 2004)
To examine the potentiality of grassland dominated with turf-type grasses, which are mainly used for the establishment of green spaces, forage production and its utilization as forage resources, dry matter yield and forage quality of three different turf-type mixtures were estimated throughout three consecutive experimental years. According to the experiment, the mean of dry matter(DM) yield, chemical composition, DM digestibility, crude protein dry matter(CPDM) and digestible dry matter(DDM) yield was not significantly different among species(p > 0.05) over three experimental years. Botanical composition of three dominant species(tall fescue, Kentucky bluegrass and perennial ryegrass) was 42, 35 and 28%, respectively, in three mixtures at the last cutting(6th) in 2001. The botanical composition of three dominated species such as tall fescue, Kentucky bluegrass and perennial ryegrass was maintained 84% of the total plants in all types of mixtures. Therefore, It is observed that the mixture types did not closely affect the botanical composition. But botanical composition of the other species such as redtop(8%) and creeping bentgrass(6${\sim}$7%) was low. Especially, that of red fescue was the least(1${\sim}$2%) of all mixed species. As mentioned above, any difference was not observed in DM yields, forage quality and botanical composition among mixture types. Therefore, any types of mixtures can be used as public green spaces like school ground areas or river-sides, and as forage resources additionally. 본 시험은 혼파조합이 하번초형 혼파초지의 건물수량과 사료가치에 미치는 영향을 구명하여 하번초형 혼파초지를 조성하는데 적합한 혼파조합을 찾고자 1998년 9월부터 2001년 12월까지 충남대학교 생명과학대학내 부속 초지시험포장에서 수행하였다. 공시 혼파조합은 tall fescue, kentucky bluegrass 및 perennial ryegrass 중심의 3가지 혼파조합을 공시하였으며 얻어진 시험결과는 다음과 같다 1) 3년 평균 ha당 건물수량, 일반화학적 성분, 건물소화율과 조단백질수량(CPDM) 및 가소화건물수량(DDM)은 혼파조합간에차이가 없었다. 2) 2001년도 6회 마지막 예취시 tall fescue, Kentucky bluegrass 및 perennial ryegrass 중심의 혼파조합에서 tall fescue, Kentucky bluegrass 및 perennial ryegrass의 식생 비율은 각각 42, 35 및 28%이었고, 전체 초종에서 이들 3초종이 차지하는 식생 비율은 모든 혼파조합에서 84%로 나타나 혼파조합이 식생비율에 미치는 영향은 크지 않았다. 기타 초종 중에서는 redtop(8%)과 creeping bentgrass(6${\sim}$7%)의 식생비율이 낮았으며, 특히 red fescue(1${\sim}$2%)는 매우 낮은 식생비율이 보였다. 이상의 결과를 종합해 볼 때, 혼파조합간에 건물수량과 사료가치 및 식생비율에 뚜렷한 차이가 없었던 것으로 보아, tall fescue, Kentucky bluegrass 및 perennial ryegrass 중심의 어느 혼파조합으로 하번초형 혼파초지를 조성하여도 공익목적과 부수적으로 생산되는 목초를 조사료원으로 활용가능성은 크다고 하겠다.